PENGARUH ARUS KAS DAN MODAL KERJA TERHADAP STRUKTUR MODAL PADA PT SUMBER ALFARIA TRIJAYA.TBK - Nainggolan, Juitro; Putra, Argo Prima (SCIENTIA JOURNAL, 2019)
The purpose of this study to determine the effect of cash flow and working capital on capital structure at PT Sumber Alfaria Trijaya Tbk.. This research is a quantitative research. The data used in this study is secondary data in the form of corporate financial statements. The population in this study is the financial statements of the company in the form of balance sheet and income statement for eight years. The sample is used with probability sampling method where all population have chance to be research sample that is 32 observation. The method of analysis in this study using multiple linear regression. The results showed that partially operating cash flow, investment, funding and working capital have no significant effect on capital structure at PT Sumber Alfaria Trijaya Tbk. Similarly, the results of the study show that operating cash flow, investment, funding and working capital have no significant effect on capital structure at PT Sumber Alfaria Trijaya Tbk.. The value of Adjusted R Square is 14.5%, it shows the variable value of operating cash flow, investment, funding and working capital able to explain the capital structure of 14.5% and the remaining 85.5% is explained by other variables not included in this study.